PENGARUH RETURN ON INVESTMENT TERHADAP HARGA SAHAM PADA PERUSAHAAN PULP AND PAPER YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dharu Witjaksono; Dewi Hasanah (The Asia Pacific Journal Of Management Studies, 2016)
This study aims to determine the effect of the Return On Investment to the stock price on the pulp and paper companies listed in Indonesia Stock Exchange. As according Kashmir bahwasannya Return On Investment could affect the stock price with a low or rising value of the Return On Investment can impact on a company's stock price.The research was conducted on pulp and paper companies in Indonesia Stock Exchange (IDX). The population in this study were 17 pulp and paper companies listed in Indonesia Stock Exchange (BEI) in the period 2005 -2013. While the sample used in this study are 4 companies. Teknikpengambilan sample is by simple random sampling. In this study the type of data used are secondary data from published Jakarta and Security Exchange (JSX) and the Indonesian Capital Market Directory (ICMD). and data analysis techniques used are simple linear regression, the product moment correlation coefficient, koefesiensi determination and hypothesis testing (t test) with the help of a software program SPSS V.20.0.From the results of the data using SPSS software (statistical package for social sciences) version 20.0 was found regression equation Y = 1447.372 + 106 076 X, seen from the t test using the t test of the two parties was 4,415 while 2,042 t table so t count> t table (4,415> 2,042) with a significance value 0.000 <0.05 then Ho is rejected and Hi is received which can be explained that there are significant between the return on investment to the stock price on the pulp and paper companies listed in Indonesia Stock Exchange (IDX). Based on the correlation analysis showed that the correlation coefficient (R) of 0.604, which means that the return on investment to the stock price has a strong relationship. Squer R value of 0.364 in this study means that the value of the two variables work positively affects 36.4% of the stock price. This means that stock prices are influenced by the Return On Investment by 36.4% while the remaining 63.6% is influenced by other factors outside of this study is the ROE, EVA, earning per share, and dividends per share.